Exploring Transactional Political Dynamics in the 2020 Regional Head Elections in Toraja Utara Regency: A Social Exchange Theory. - Isak Pasulu (Proceeding of The International Conference on Economics and Business, 2023)
This study analyzes the patterns of transactional politics between candidates and donors in the 2020 Simultaneous Regional Head Elections in Toraja Utara Regency. By adopting the perspective of social exchange theory, this research reveals the dynamics of the relationship between candidates and donors in soliciting financial support for their campaigns. A qualitative descriptive method was employed to gather data through in-depth interviews, observations, and documentation. The research findings indicate that the required funding for candidates ranged from 50 to 80 billion IDR during the 2020 regional elections. This study illustrates that fundraising through family/relatives is carried out based on the strength of emotional ties and shared values within Toraja culture, while businesspersons offer support in order to gain future political advantages and power. The theoretical implications of this research link the relationship between intrinsic and extrinsic exchanges, highlighting their impact on political dynamics and social change in the region.